Bulbus Fritillariae Cirrhosae as a Respiratory Medicine: Is There a Potential Drug in the Treatment of COVID-19? - Quan, Yunyun; Li, Li; Yin, Zhujun; Chen, Shilong; Yi, Jing; Lang, Jirui; Zhang, Lu; Yue, Qianhua; Zhao, Junning (Frontiers in Pharmacology, 2022)
Bulbus Fritillariae cirrhosae (BFC) is one of the most commonly used Chinese medicines for lung disease, and exerts antitussive, expectorant and anti-inflammatory, anti-asthmatic, anti-oxidant effects, which is an ideal therapeutic drug for respiratory diseases. Through this review, it was found that the therapeutic mechanism of BFC on respiratory diseases exhibits the characteristics of multi-components, multi-targets and multi signaling pathways. In particular, the therapeutic potential of BFC for COVID-19 is a huge discovery in terms of intervention of “cytokine storm”, STAT, NF-κB, and MAPK signaling pathways, as well as the renin-angiotensin system (RAS) that ACE is involved in. BFC is very likely to become a potential drug for the treatment of COVID-19. This review summarized the research progress of BFC in the respiratory diseases, discussed the development potentiality of BFC for the treatment of COVID-19, explained the chemical diversity and biological significance of the alkaloids in BFC, clarified the material basis, molecular targets and signaling pathways of BFC for the respiratory diseases, which will help guide the further study of the application of BFC.